Some Geochemical, textural and Radioactive Characteristics of the Sandstorms Loads Blown over Baghdad and Ramadi Cities, Middle Iraq - Al-Dabbas, Moutaz; Al- Khafaji, Raad (Iraqi Journal of Science, 2024)
The present study examined the characteristics of dust from sandstorms that occurred over Baghdad and Ramadi cities, middle of Iraq, from February 2009 to July 2010. The texture of the dust samples were ranged from sandy silty clay (71.4%) to sandy clayey silt (28.6 %).The mineralogical composition of the sand fractions included Quartz (52.2%, ), feldspar (6.4%, ), calcite (33%, ), gypsum (5.6%, ), dolomite (1.5%,) and heavy minerals (1.3%,). The clay minerals present included Chlorite, Illite, Montmorillonite, Palygorskite and Kaolinite. The results of heavy minerals analyses indicated that they were opaque heavy mineral, pyroxene, hornblende, zircon, chlorite, epidote and garnet.The Uranium concentration average absorbed dose and average external effective dose were calculated for dust of sandstorm at 2-4/7/2009 and 3-4/4/2010 for both cities Baghdad and Ramadi. The results for specific activity of uranium were in range of (5.43-9.56 Bg/kg) and the absorbed dose range (2.19- 5.46 nGy/h)for sandstorm at 2-4/7/2009 and the average specific activity of uranium was in range of (7.32- 18.96 Bg/kg) and the average absorbed dose (3.27- 8.98 nGy/h) for sandstorm 3-4/4/2010. All the results were lower than critical dose level, but